2003
DOI: 10.1002/cne.10988
|View full text |Cite
|
Sign up to set email alerts
|

Expression of vesicular glutamate transporters in rat lumbar spinal cord, with a note on dorsal root ganglia

Abstract: Three vesicular glutamate transporters (VGLUTs) have been recently identified and their distribution has been mapped in various brain areas. In the present study, we used morphological approaches to investigate their expression in the rat lumbar spinal cord and dorsal root ganglia. Our results show a complementary distribution of VGLUT-expressing fibers in the spinal cord, with no overlapping in nerve endings. In the dorsal horn, VGLUT1 is most abundant in mechanosensory/proprioceptive deep afferent fibers. VG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

34
146
5
2

Year Published

2005
2005
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(187 citation statements)
references
References 42 publications
34
146
5
2
Order By: Relevance
“…As previously reported, [2,34,53] VGlut2 labeling was found to be distributed throughout the spinal gray matter and was particularly abundant in the superficial dorsal horn (laminae I and II; figure 3A) and in lamina IV. Therefore, some overlap of labeling of fos-I nuclei and VGlut2 was found in all regions after pudendal and pelvic nerve stimulation, but this overlap was most prominent in the dorsal horn and DGC (figure 3H).…”
Section: Double Immunocytochemistrysupporting
confidence: 85%
See 3 more Smart Citations
“…As previously reported, [2,34,53] VGlut2 labeling was found to be distributed throughout the spinal gray matter and was particularly abundant in the superficial dorsal horn (laminae I and II; figure 3A) and in lamina IV. Therefore, some overlap of labeling of fos-I nuclei and VGlut2 was found in all regions after pudendal and pelvic nerve stimulation, but this overlap was most prominent in the dorsal horn and DGC (figure 3H).…”
Section: Double Immunocytochemistrysupporting
confidence: 85%
“…The present study examined the relationship of VGlut2, VGlut3 transporters and NKI receptors with fos-I nuclei as both glutamate and NKI receptors have been shown to regulate pelvic reflexes [64,69]. Glutamate is the major excitatory neurotransmitter and recent studies have documented the distribution of glutamate transporters in the lumbosacral cord [2,34,38,51,57,63]. Studies have suggested that VGlut1 and VGlut2 expression is restricted to glutaminergic neurons; however, VGlut3 expression is found not only in glutaminergic neurons but also neurons that contain acetylcholine and serotonin [28].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Three types of VGluTs, VGluT-1, -2, and -3, have been identified in the CNS (23). Although VGluT-1͞2 transcripts have been detected in rat spinal motoneurons (28,29), no VGluT-1͞2 proteins have been found to colocalize with VAChT (28,30) or ChAT (31). Recent studies demonstrating VGluT-2 immunostaining in motoneuron collateral axons projecting to layer VII of the spinal cord (28,32) confirmed the lack of VGluT-2 and glutamatergic transmission in the cholinergic projections to the NMJ.…”
Section: Discussionmentioning
confidence: 99%